The population of Brussels: a demographic overview - Patrick Deboosere; Thierry Eggerickx; Etienne Van Hecke; Benjamin Wayens (Brussels Studies)
The Brussels-Capital Region is comprised of 19 municipalities and has a surface area of 161.4 km². The region is the core of a much broader morphological agglomeration made up of 36 municipalities with a total population of more than one and a half million inhabitants. The official population of the Brussels-Capital Region totalled 1 048 491 inhabitants on 1st January 2008 and is the youngest in the country with an average age of 37.8 years recorded in 2006. The demographic development of Brussels has always been strongly dominated by migration over the past one and half centuries and this is not different today. The capital city has experienced a rise in population over the past few years and, just like all large European cities, the population composition is highly influenced by internationalisation. The last census (socio-economic survey of 2001) enabled the nationality of origin to be taken into account. According to this criterion, Brussels had 45 different nationalities with at least 1 000 inhabitants. The composition has diversified further since then and there has been an increase in inhabitants from European Union countries. The region is characterised by a clear spatial differentiation between the poorer districts, mixed neighbourhoods and the affluent areas of the city. The underlying structure of this spatial segregation according to socio-economic status has deep-seated historical roots and a high level of inertia. However, the arrival of new inhabitants, large construction sites within a number of districts, speculation and increasing property prices are slowly changing the composition of the population within some districts. A short description of the most important demographic trends that will affect the composition of the city in the coming decades is given below.